A structural overview of the zinc transporters in the cation diffusion facilitator family. Issue 4 (16th April 2019) - Cotrim, Camila A.; Jarrott, Russell J.; Martin, Jennifer L.; Drew, David
Abstract : A summary is provided of the last five years of structural studies of bacterial YiiP, providing an overview of how zinc‐transporter membrane proteins operate at the molecular level. Abstract : The cation diffusion facilitators (CDFs) are a family of membrane‐bound proteins that maintain cellular homeostasis of essential metal ions. In humans, the zinc‐transporter CDF family members (ZnTs) play important roles in zinc homeostasis. They do this by facilitating zinc efflux from the cytoplasm to the extracellular space across the plasma membrane or into intracellular organelles. Several ZnTs have been implicated in human health owing to their association with type 2 diabetes and neurodegenerative diseases. Although the structure determination of CDF family members is not trivial, recent advances in membrane‐protein structural biology have resulted in two structures of bacterial YiiPs and several structures of their soluble C‐terminal domains. These data reveal new insights into the molecular mechanism of ZnT proteins, suggesting a unique rocking‐bundle mechanism that provides alternating access to the metal‐binding site.